2018
DOI: 10.1111/jcpt.12695
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of serum creatinine‐based formulae estimating renal function in non‐critically ill surgery patients: Focus on augmented renal clearance

Abstract: In surgical patients, eGFR frequently underestimates measured CrCl, especially in young patients with low ASA score. eGFR cut-offs predicting ARC were identified.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…Different studies assessed the performances of eGFR equations compared to mCL CR across different ranges of GFR, and almost all showed important flaws when using such mathematical equations for renal function estimation in critically ill patients [ 22 , 23 , 24 , 25 ]. A recent retrospective study conducted on 237 critically ill patients in Arabia with a mean mCL CR of 102.7 ± 65.4 mL/min showed that eGFR CKDEPI , eGFR CG , and eGFR MDRD had an accuracy as low as 12.7–30% in estimating mCL CR within ±10%, and that both eGFR CG and eGFR MDRD , but not eGFR CKDEPI , were significantly biased.…”
Section: Discussionmentioning
confidence: 99%
“…Different studies assessed the performances of eGFR equations compared to mCL CR across different ranges of GFR, and almost all showed important flaws when using such mathematical equations for renal function estimation in critically ill patients [ 22 , 23 , 24 , 25 ]. A recent retrospective study conducted on 237 critically ill patients in Arabia with a mean mCL CR of 102.7 ± 65.4 mL/min showed that eGFR CKDEPI , eGFR CG , and eGFR MDRD had an accuracy as low as 12.7–30% in estimating mCL CR within ±10%, and that both eGFR CG and eGFR MDRD , but not eGFR CKDEPI , were significantly biased.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, beta-lactam optimization by means of TDM may acquire special relevance for patients with augmented renal function, a condition that often occurs in oncohematologic patients [ 48 ]. In this patient population, dose adjustments should be based on measured rather than estimated renal function, as eGFR has been reported to either underestimate or overestimate measured creatinine clearance in different studies [ 49 , 50 ].…”
Section: Discussionmentioning
confidence: 99%